Forecast of greenhouse gas emissions and absorption of forestry activities in Russia - Morkovina Svetlana; Kolesnichenko Elena; Yakovenko Nataliya; Sheshnitsan Sergey; Vodolazhsky Alexey; Pryadilina Natalia; Manmareva Valeria (BIO Web of Conferences)
The article analyzes and quantifies greenhouse gas emissions and absorption in the territories of the forest fund in different regions of Russia. Scenarios have been developed to predict the net absorption of greenhouse gases by forest managers until 2050, and a long-term forecast of the balance of emissions and absorption of these gases has been presented, taking into account changes in strategic forest planning documents. According to forecasts, greenhouse gas emissions associated with the implementation of sanitary and wellness measures will amount to at least 2.3 million by 2028. tons of CO2 equivalent annually, maintaining the level of 2018. More than 60% of these emissions will occur in the Siberian and Central Federal Districts. The potential for reducing emissions in this case is limited, because the actual area of implementation of activities has significantly decreased from 2012 to 2018. The implementation of the target scenario only through the country’s forestry sector will not allow achieving the target volume of net forest absorption set by the Strategy for 2050. A deficit of 279.7 million tons of CO2 equivalent per year between the target scenario and the planned net absorption volume (at least 1,158 million tons). t CO2-eq. per year) can be overcome through additional measures, including climate projects in the field of forestry and afforestation on lands of other categories. In order to maintain carbon runoff in Russian forests, additional protection and restoration measures are needed, which go beyond the existing plans of the subjects.